Contingent Behavior and Asymmetric Preferences for Baltic Sea Coastal Recreation - Bertram, Christine; Ahtiainen, Heini; Meyerhoff, Jürgen; Pakalniete, Kristine; Pouta, Eija; Rehdanz, Katrin (Kluwer Academic Publishers, 2020)
In this study, we augment the traditional travel cost approach with contingent behavior data for coastal recreation. The objective is to analyze the welfare implications of future changes in the conditions of the Baltic Sea due to climate change and eutrophication. Adding to the literature, we assess the symmetricity of welfare effects caused by improvements and deteriorations in environmental conditions for a set of quality attributes. Responses are derived from identical online surveys in Finland, Germany and Latvia. We estimate recreational benefits using linear and non-linear negative binomial random-effects models. The calculated annual consumer surpluses are considerably influenced by the magnitude of the environmental changes in the three countries. We also observe asymmetries in the effects of environmental improvements and deteriorations on the expected number of visits. In particular, the results indicate that deteriorations lead to larger or more significant impacts than improvements in the case of blue-green algal blooms and algae onshore for Finland, water clarity for Germany, and water clarity and blue-green algal blooms for Latvia. For the remaining attributes, the effects are ambiguous.
Keywords: Baltic Sea; Recreational benefts; Valuation; Contingent behavior; Eutrophication; Climate change; Water quality; Asymmetric preferences